Can digital governance stimulate green development? Evidence from the program of “pilot cities regarding information for public well-being” in China - Xuxin Zou; Jiadi Min; Shuang Meng; Wenguan Dai; Xinyang Li (Frontiers in Public Health, 2025)
Digital governance is an important goal of government digital transformation, and the policy of “pilot cities regarding information for public well-being” in China is an important initiative to promote the reform of government governance system and realize green development. Based on the panel data of 282 cities in China from 2007 to 2020, this paper analyzes the mechanism and path of the impact of digital governance on green development using the program of “pilot cities regarding information for public well-being” as a quasi-natural experiment. The double-difference model and mediation effect model are utilized. The results show that digital governance can significantly promote green development, and the path of influence is the supererogation and the rationalization of industrial structure, i.e., digital governance can promote the green development of the cities by enhancing the supererogation and the rationalization of industrial structure. In addition, there is obvious heterogeneity in the impact of digital governance on green development. The policy exerts a stronger effect on economically developed cities than on economically backward cities, and a stronger effect on large cities than on small- and medium-sized cities. Therefore, the relevant departments should continue to optimize the pilot policy regarding information for public well-being, strive to improve the government’s digital governance, focus on economically backward cities and small-sized cities, actively cultivate the green development, promote the optimization and upgrading of industrial structure, and vigorously support cross-regional exchanges and cooperation, so as to jointly achieve green and high-quality development.